The Role of the Nutritious Meal Program (PMB) on Physical Education Learning Participation of Students with Physical Disabilities at SLB Negeri 1 Buleleng - Cahyo Subekti; Erick Burhaein (Jurnal Pendidikan Jasmani (JPJ), 2026)
This study aims to analyze the role of the Nutritious Meal Program (PMB) on the participation of students with disabilities in Physical Education, Sports, and Health (PJOK) learning at SLB Negeri 1 Buleleng. This study used a qualitative approach with a case study design. The research informants consisted of the principal, class teachers, and two PJOK teachers selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles, Huberman interactive model. The results showed that PMB played a significant role in improving students' physical readiness, energy, and concentration, thus enabling them to participate in PJOK learning more optimally. In addition, PMB contributed to increased learning participation, characterized by activeness in following instructions, enthusiasm in trying new movements, involvement in group activities, and consistent attendance. The success of the program was also influenced by the support of the principal and teachers, as well as the implementation of adaptive learning methods that are appropriate to students' physical abilities. This study concluded that PMB not only meets students' nutritional needs but also serves as an important strategy in inclusive education, increasing motivation, social engagement, and active participation of students with physical disabilities in PJOK learning.